Stuck at the Bottom? Gender and Immigrants’ Entrapment in Low-skilled Work - Grönlund, Anne; Nordlund, Madelene (Nordic Journal of Working Life Studies, 2024)
Immigrant women are widely portrayed as facing a serious labor market disadvantage, yet gender differences in immigrants’ occupational mobility have been little explored. The article studied gender gaps in immigrants’ occupational entrapment, defined as entering and remaining in low-skilled/low-prestige work rather than moving on to more skilled/prestigious work. The analyses were based on longitudinal register data and followed five immigrant cohorts arriving in Sweden in the early 2000s over a 12-year period. The results show that immigrant women were more likely than men to start out in a low-skilled/low-prestige job and less likely to experience occupational mobility. However, tertiary education strongly mitigated these gender gaps. At the same time, the differences between high- and low-educated individuals widened more among women than among men. Family-related factors and country-specific human capital did not explain these patterns, but the findings indicate that occupational gender segregation can be crucial to immigrants’ mobility prospects.